FORMATION OF CIVIC IDENTITY IN SCHOOLCHILDREN DURING MATHEMATICS EDUCATION IN GRADES 5-6 - Shvets, Vasyl; Martyniuk, Kateryna (Physical and Mathematical Education, 2025)
Formulation of the problem. The State Standard of Basic Secondary Education of Ukraine states that the formation of civic identity is a key competency that should be integrated into the educational process. In the fifth and sixth grades, when students form an initial understanding of social roles and responsibilities, it is important not only to impart subject knowledge but also to develop civic awareness. Mathematics as an academic discipline has a significant potential to form civic identity through tasks that model social situations, require logical reasoning, assessing the fairness of decisions, comparing alternatives, and making responsible decisions. Materials and methods. To obtain the results, we used theoretical (analysis of regulatory documents, reference and educational literature on the theory and methods of teaching mathematics, synthesis of the data obtained, and their generalization) and empirical (survey of teachers, familiarization with the best practices of teaching mathematics to students, and survey of students) methods of scientific knowledge. Results. The article proposes methodological approaches to the formation of civic identity in students of grades 5-6 in the course of mathematics, and provides examples of applied problems with an analysis of their solutions and relevant methodological comments to them. Conclusions. One of the ways to form civic identity in students of grades 5-6 is to solve practice-oriented tasks and applied problems whose plots reflect civic life in Ukraine. It is important that this process is accompanied by meaningful information content and that the educational programs for future mathematics teachers continue to adapt to modern challenges, providing students with the knowledge and skills necessary to actively participate in the life of Ukraine.